Identification of a Systemic Lupus Erythematosus Risk Locus Spanning ATG16L2, FCHSD2, and P2RY2 in Koreans. Issue 5 (27th April 2016) - Lessard, Christopher J.; Sajuthi, Satria; Zhao, Jian; Kim, Kwangwoo; Ice, John A.; Li, He; Ainsworth, Hannah; Rasmussen, Astrid; Kelly, Jennifer A.; Marion, Miranda; Bang, So‐Young; Bin Joo, Young; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder whose etiology is incompletely understood, but likely involves environmental triggers in genetically susceptible individuals. Using an unbiased genome‐wide association (GWA) scan and replication analysis, we sought to identify the genetic loci associated with SLE in a Korean population. Methods: A total of 1, 174 SLE cases and 4, 246 population controls from Korea were genotyped and analyzed with a GWA scan to identify single‐nucleotide polymorphisms (SNPs) significantly associated with SLE, after strict quality control measures were applied. For select variants, replication of SLE risk loci was tested in an independent data set of 1, 416 SLE cases and 1, 145 population controls from Korea and China. Results: Eleven regions outside the HLA exceeded the genome‐wide significance level ( P  = 5 × 10 −8 ). A novel SNP–SLE association was identified between FCHSD2 and P2RY2, peaking at rs11235667 ( P  = 1.03 × 10 −8, odds ratio [OR] 0.59) on a 33‐kb haplotype upstream of ATG16L2 . In the independent replication data set, the SNP rs11235667 continued to show a significant association with SLE (replication meta‐analysis P  = 0.001, overall meta‐analysis P  = 6.67 × 10 −11 ; OR 0.63). Within the HLA region, the SNP–SLE association peaked in the class II region at rs116727542, with multiple independent effects observed in this region. Classic HLA allele imputation analysis identified HLA–DRB1*1501 and HLA–DQB1*0602, each highly correlated with one another, as most strongly associated with SLE. Ten previously established SLE risk loci were replicated: STAT1 – STAT4, TNFSF4, TNFAIP3, IKZF1, HIP1, IRF5, BLK, WDFY4, ETS1, and IRAK1 – MECP2 . Of these loci, previously unreported, independent second risk effects of SNPs in TNFAIP3 and TNFSF4, as well as differences in the association with a putative causal variant in the WDFY4 region, were identified. Conclusion: Further studies are needed to identify true SLE risk effects in other loci suggestive of a significant association, and to identify the causal variants in the regions of ATG16L2, FCHSD2, and P2RY2 .